2020
DOI: 10.1074/jbc.ra120.013067
|View full text |Cite
|
Sign up to set email alerts
|

A Legionella effector kinase is activated by host inositol hexakisphosphate

Abstract: The transfer of a phosphate from ATP to a protein substrate, a modification known as protein phosphorylation, is catalyzed by protein kinases. Protein kinases play a crucial role in virtually every cellular activity. Recent studies of atypical protein kinases have highlighted the structural similarity of the kinase superfamily despite notable differences in primary amino acid sequence. Here, using a bioinformatics screen, we searched for putative protein kinases in the intracellular bacterial pathogen Legionel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 54 publications
(59 reference statements)
0
21
0
Order By: Relevance
“…Using a genetic approach, we exclude inositol pyrophosphate species as being necessary for OspB activity and define the inositol phosphate species requirement as IP 6 ; however, it is possible that an inositol pyrophosphate species may be sufficient for stimulating activity in vitro , as found for IP 7 and C. difficile TcdB (Savidge et al, 2011). The requirement for a host-specific cofactor, such as IP 6 , ubiquitin, calmodulin, or cyclophilins, for the activation bacterial effectors is increasingly appreciated (Anderson et al, 2011; Coaker et al, 2005; Drum et al, 2002; Mittal et al, 2010; Sreelatha et al, 2020; Tyson & Hauser, 2013) and necessarily restricts enzymatic activity to the context of host infection. Together, these findings provide strong evidence that OspB is a cysteine protease in the family of proteases represented by the cysteine protease domains of the MARTX toxins and large clostridial cytotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…Using a genetic approach, we exclude inositol pyrophosphate species as being necessary for OspB activity and define the inositol phosphate species requirement as IP 6 ; however, it is possible that an inositol pyrophosphate species may be sufficient for stimulating activity in vitro , as found for IP 7 and C. difficile TcdB (Savidge et al, 2011). The requirement for a host-specific cofactor, such as IP 6 , ubiquitin, calmodulin, or cyclophilins, for the activation bacterial effectors is increasingly appreciated (Anderson et al, 2011; Coaker et al, 2005; Drum et al, 2002; Mittal et al, 2010; Sreelatha et al, 2020; Tyson & Hauser, 2013) and necessarily restricts enzymatic activity to the context of host infection. Together, these findings provide strong evidence that OspB is a cysteine protease in the family of proteases represented by the cysteine protease domains of the MARTX toxins and large clostridial cytotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…S1B). IP6 binding in the allosteric site showed that binding of a highly negatively charged IP6 coordinates several lysine side chains (Lys 76, Lys107, and Lys111) from the previously disordered region of the N-lobe and restores the ATP binding site [52].…”
Section: Phosphorylation Of Host Proteinsmentioning
confidence: 99%
“…Our lab has previously taken a bioinformatic approach to identify atypical and uncharacterized members of the protein kinase superfamily. Several of the outlying kinase families we have characterized are components of bacterial conflict systems, including the HopBF1 substrate of the Pseudomonas syringae type III secretion system (1) and the Lpg2603 and SidJ substrates of the Legionella pneumophila Type IV secretion system (T4SS) (2,3). Legionella is a gram-negative environmental pathogen and the causative agent of a potentially fatal pneumonia called Legionnaire's disease.…”
Section: Introductionmentioning
confidence: 99%